The enigma, language of Parmenides - Posada González, María Cecilia (Estudios de Filosofía, 2006)
It is often forgotten that the pre-Socratics, more than "philosophers" in the current sense of the word, were men who were considered wise by their contemporaries. Here is a small sample of how far the Poem of Parmenides is from the kind of conceptual language that the West calls "philosophical." The language of the eléata is a living and creative word like that of poets, but also dark and ambiguous like that of the gods. Whoever reads Parmenides from the perspective of Western metaphysics and ignores its poetic, religious, political and "pre-conceptual", may end up far from their original thought.